Channel shifting of Narayani River and its ramification in west Chitwan, central Nepal (Journal of Nepal Geological Society, 2004)
The analysis of satellite imageries and topographic maps of different dates revealed that the Narayani River near Mangalpur migrated about 32 km to the west. Its westward shift is also clearly evidenced by the continuation of wetlands parallel to the main river course. The interpolated contours of 2 m interval obtained from the topographic map of 1:25,000 scale also revealed many parallel depressions. These depressions belong to an old abandoned channel, and are closely associated with a sharp bend of the Narayani River. There is a high possibility of breaching a weak and unconsolidated natural levee, which is currently protecting the abandoned channel from flooding. The flood disaster after the breach is inevitable and it can devastate the six Village Development Committees situated within the abandoned channel.